PROFITABILITY, LIQUIDITY, LEVERAGE, AND FIRM RISK: EVIDENCE FROM INDONESIAN TOBACCO INDUSTRY - Amrie Firmansyah; Nabilla Salsa Fahira; Aulia Amira (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study examines the effect of profitability, liquidity, and leverage on company risk. The research sample used cigarette companies listed on the Indonesia Stock Exchange quarterly from 2013 to 2019. This research data uses secondary data in financial information, financial reports, and stock information obtained from the website www.finance.yahoo.com and www.idnfinancials.com. Based on purposive sampling, this study obtained a total sample of 112 observations. The data analysis method used data regression analysis for panel data. The results showed that profitability and liquidity positively affect firm risk, while leverage does not affect firm risk. This study indicates that financial performance is closely related to stock price risk in the Indonesian cigarette industry